IOT Soft Starter Revolutionizes Single-Phase Induction Motor Control: IOT Soft Starter Merevolusi Kontrol Motor Induksi Fase Tunggal - Hadiyatulloh, Moh; Wisaksono, Arief (Indonesian Journal of Innovation Studies, 2024)
Induction motors often face issues with large initial currents that can disrupt networks and damage the motors. This study designs a soft starter for single-phase induction motors using an IoT-based Arduino Uno system to regulate initial current surges and enable remote monitoring via the Blynk App. The system uses the AC Light Dimmer module controlled by Arduino Uno and Wemos D1 Mini microcontrollers, with the PZEM-004T sensor detecting current and voltage. Experimental results showed a significant reduction in initial current, averaging 0.48 A and 201.90 V within 10 seconds. Additionally, the system allows for monitoring from up to 16 km away using an Android smartphone, providing an effective solution for managing induction motor performance and ensuring reliable operation. Highlight: Renewable technology for controlling single-phase induction motor initial current. Software and system flowcharts illustrate IoT-based motor control. Significant reduction in initial current demonstrated in induction motor testing. Keywoard: Induction Motors, Soft Starter, IOT, Arduino Uno, Remote Monitoring.